Impact of Noise on Early Development and Hearing in Zebrafish (Danio rerio) - Lara, Rafael Ayala (University of Saint Joseph, 2020)
Fishes are highly specialized in extracting ecologically relevant information from their diverse acoustic habitats since early developmental stages. The zebrafish (Danio rerio) is a valuable and well-stablished vertebrate model for investigating hearing functioning and disorders, development of the inner ear in vertebrates including humans, drug discovery, ecotoxicology assessments and behavioral research. Although the acoustic environment is known to shape the structure and sensitivity of auditory systems, there is no information on the natural soundscape of this species. Zebrafish are typically reared in large-scale artificial housing systems, which acoustic properties and potential effects on hearing remain largely unknown. Even though elevated levels of noise are widely present in most aquatic soundscapes and to an even greater extent in artificial environments, very limited information is known on how this important environmental stressor impacts species’ development and physiology, hearing capabilities and inner ear morphology, and behaviour. Considering that noise pollution is rapidly increasing in aquatic ecosystems, causing detrimental effects on survivability and growth and altering physiology and behaviour of organisms, it is of paramount importance to assess how this stressor affects wildlife, especially in early ontogeny, a critical period for development and establishment of phenotypic traits. For this thesis I aimed to 1) characterize the soundscape of both zebrafish natural habitats and laboratory captive conditions, and discuss possible impact on auditory sensitivity. Sound recordings were conducted in five distinct zebrafish habitats (Southwest India), from quieter stagnant environments with diverse biological/abiotic sounds to louder watercourses characterized by current and moving substrate, while artificial environmental characterization was conducted on three typical zebrafish housing systems. 8 In order to assess the impact of noise exposure on early development, my next goal was to 2) perform a split-brood experiment to test the effects of chronic noise exposure to increasing levels (130 and 150 dB re 1 μPa, continuous white noise) and different temporal regimes (mimicking shipping activity) on larval zebrafish in regards to general development, physiological stress, and behavioural patterns. Finally, the last objective consisted on 3) testing the effects of chronic noise exposure on auditory sensitivity measured based on inner ear saccular microphonics and acoustic-evoked startle responses (prepulse inhibition paradigm) in larval zebrafish, as well as evaluating whether sensitivity changes were paralleled by altered inner ear morphology. Based on bioacoustics methods, my first study found that zebrafish natural soundscape varied between 98 and 126 dB re 1 lPa in sound pressure levels. Sound spectra presented most energy below 3000 Hz and quieter noise windows were found in the noisiest habitats matching the species best hearing range. Contrastingly, recordings from zebrafish housing systems revealed higher sound levels (122–143 dB) and most energy below 1000Hz with more spectral peaks, which might cause significant impact such as auditory masking or even hearing loss. In my second research work, the acoustic treatments did not affect general development or hatching but increased noise levels led to a significant increase in mortality of larval zebrafish. The cardiac rate, yolk sac consumption and cortisol levels increased significantly with increasing noise level at both 3 and 5 dpf (days post fertilization). Variations in noise time presentations (different random noise periods similar to shipping activity) suggested that the presence of longer silent intervals is important to down-regulate physiological stress. Moreover, 5 dpf larvae exposed to 150 dB continuous noise regimes displayed increased dark avoidance in an anxiety-related dark/light preference test and displayed a significant 9 impairment in spontaneous alternation behaviour (SAB) a memory and sensorimotor related behaviour. Finally, in the last thesis goal, I found that noise-exposed specimens displayed significantly lower hair cell number and saccular epithelial area. This change in sensory morphology was paralleled by a significant decrease in inner ear saccular sensitivity at lower frequencies (100 to 200 Hz) in 5 dpf larvae. Sensorimotor hearing assessment revealed a hypersensitisation effect in noise-exposed group that displayed higher startle swimming velocity, but also significant decrease in sensitivity at 200 Hz. Altogether, this thesis provides an important ground for future research on the adaptation of zebrafish auditory system to the natural soundscapes, and highlights the importance of controlling noise conditions in captivity systems. Furthermore, results provide first evidence of noise-induced physiological stress, anxiety-driven behaviours and memory impairment in larval zebrafish larvae, showing that both noise amplitude and timing may negatively impact key physiological and behavioural endpoints in early ontogeny. The thesis also reports new findings on how acoustic stress may impact the structure and function of the inner ear in larval fish, which was followed by decreased sensitivity in sensorimotor responses to acoustic stimuli. My research highlights the importance of investigating how altered soundscapes and associated physiological and behavioural stress may affect important sensitive windows in development and impose new evolutionary challenges under a scenario of global change
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph